2019
DOI: 10.1093/ajcn/nqy266
|View full text |Cite
|
Sign up to set email alerts
|

Complementary feeding and micronutrient status: a systematic review

Abstract: BackgroundProper nutrition during early life is critical for growth and development.ObjectivesThe aim was to describe systematic reviews conducted by the Nutrition Evidence Systematic Review team for the USDA and the Department of Health and Human Services Pregnancy and Birth to 24 Months Project to answer the following: What is the relation between 1) timing of introduction of complementary foods and beverages (CFBs) or 2) types and/or amounts of CFBs consumed and micronutrient status (iron, zinc, vitamin D, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 43 publications
1
31
0
4
Order By: Relevance
“…EFSA staff hand‐searched through the bibliography of: −the studies included from all the searches described above, −the systematic reviews (those performed by USDA (English et al., , English et al., ; Obbagy et al., ; Obbagy et al., ; Obbagy et al., ) and published shortly before the launch of the public consultation on this Scientific Opinion were searched during the public consultation and relevant papers were added thereafter), −the theses found through the search of grey literature undertaken by the external contractor. …”
Section: Data and Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…EFSA staff hand‐searched through the bibliography of: −the studies included from all the searches described above, −the systematic reviews (those performed by USDA (English et al., , English et al., ; Obbagy et al., ; Obbagy et al., ; Obbagy et al., ) and published shortly before the launch of the public consultation on this Scientific Opinion were searched during the public consultation and relevant papers were added thereafter), −the theses found through the search of grey literature undertaken by the external contractor. …”
Section: Data and Methodologiesmentioning
confidence: 99%
“…For micronutrient status, Obbagy et al. () found moderate evidence that introducing CFs at 4 months of age compared with 6 months does not affect iron status, derived from evidence generated in high‐income countries.…”
Section: Introductionmentioning
confidence: 99%
“…Вместе с тем другие исследователи считают, что значимость различий в сроках введения густой пищи и ее качестве (специфика продукта) преувеличена: связь характеристик прикорма и отдаленных последствий для здоровья младенцев не подтверждена [25]. В связи с этим рекомендовано предлагать младенцам продукты с различными вкусами и текстурой, включая горьковатые зеленые овощи [17], поскольку разнообразные растительные продукты помогут обеспечить ребенка необходимыми микроэлементами и витаминами, прежде всего железом, цинком, фолатами, витамином В 12 [26].…”
Section: раннее пищевое программирование и особенности введения блюд unclassified
“…Some studies have reported that >90 % of the Fe requirements of a breast-fed infant must be met by complementary foods (26) . Recently, one review of studies mostly from developed countries concluded that complementary feeding with substantial amounts of Fe, such as meats or Fe-fortified foods, could provide an adequate amount of Fe or prevent Fe deficiency for breast-fed infants who were not receiving adequate Fe from another source (27) . However, the corresponding effects of these Fe-rich or Fe-fortified foods on child development outcomes were inconsistent (28) .…”
mentioning
confidence: 99%
“…Similarly, protein is associated with the global development of the brain (29) , but the evidence on association between complementary high protein-based foods and child cognitive development is lacking. Furthermore, the association of timing of introducing complementary foods, one key aspect of complementary feeding which might be associated with micronutrient status among infants (27) , with development outcomes also remains unclear (28) .…”
mentioning
confidence: 99%